Fostering National Identity Through Sustainable Heritage Conservation: Ushaiger Village as a Model for Saudi Arabia - Silvia Mazzetto (Heritage)
As the Middle East experiences rapid growth due to its oil wealth, there is a pressing need to balance contemporary development with the preservation of its rich cultural heritage. This study focuses on Ushaiger Village in Saudi Arabia, an example of traditional Najid architecture that was once abandoned and has now been brought back to life through restoration. This research tracks the restoration steps, looks at how old buildings are being reused today, and assesses the effectiveness of these efforts through a survey of 80 local residents and tourists. The results show significant improvements in preserving the village, with over 100 buildings restored using traditional, environmentally friendly materials like mud and limestone. This restoration has won strong support from the community and has boosted the local economy by increasing tourism and supporting local businesses, aligning well with Saudi Arabia’s Vision 2030 goals. This study illustrates that caring for heritage sites can promote economic and environmental health, providing a model for integrating cultural heritage into national development plans. Ushaiger Village’s story highlights the benefits of thoughtful conservation, showing that it can enhance community life and keep cultural identities alive within the Saudi Vision 2030.